Long-term trends in heavy metal contamination of marine sediments in the Arabian Gulf: A meta-analysis - S. Swetha (22827938) (2025)
Heavy metal (HM) contamination in marine sediments is a critical environmental concern due to its potential ecological and human health impacts. This study provides a comprehensive assessment of the spatial and temporal evolution of HM contamination in Arabian Gulf sediments over a 33-year period (1991–2024). Contamination levels were evaluated using key sediment quality indices such as the contamination factor (CF), geoaccumulation index (Igₑₒ), pollution load index (PLI), and ecological risk index (ERI) based on available meta-data. Spatial analysis revealed that marine sediments along the Iranian and Saudi Arabian coasts exhibited higher contamination levels compared to those of other Gulf countries. This elevated contamination is likely attributed to industrial discharges, oil spills and effluent releases from desalination plants. Arsenic (As), cadmium (Cd), copper (Cu), nickel (Ni), and lead (Pb) emerged as the primary toxic contributors to sediment pollution. Overall, HM contamination status in the region is predominantly low to moderate, with localized hotspots near industrialized coastal zones. The study highlights the need for scientifically informed waste management strategies to mitigate HM contamination, particularly in nearshore environments impacted by industrial activities. Furthermore, it recommends the implementation of continuous monitoring programs to track temporal trends and identify emerging contamination sources. These findings provide critical insights for environmental managers and policymakers in developing sustainable pollution mitigation frameworks and enhancing the resilience of marine ecosystems in the Arabian Gulf. Other Information Published in: Environmental Monitoring and Assessment License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10661-025-14348-0